Sex-specific differences in recurrence and progression following cytostatic intravesical chemotherapy for non-muscle invasive urothelial bladder cancer (NMIBC) - Laila Schneidewind; Bernhard Kiss; Thomas Neumann; Jennifer Kranz; Friedemann Zengerling; Sebastian Graf; Annabel Graser; Annemarie Uhlig (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose To systematically analyze gender-specific differences in recurrence-free survival (RFS), progression-free survival (PFS), cancer-specific survival (CSS), and overall survival (OS) as well as adverse events and quality of Life (QoL) as secondary aims in NMIBC patients undergoing cytostatic intravesical chemotherapy. Methods A systematic review and meta-analysis were conducted on studies published between 1976 and 2024, following PRISMA guidelines. MEDLINE, Embase and Cochrane Library were used as literature sources. No restrictions were made concerning language, study region or publication type. Data from 12 studies encompassing 1,527 patients were analyzed. Outcomes were assessed using random-effects models, with gender as a primary variable of interest. A risk of bias assessment was done using the ROBINS-I tool or RoB2 as appropriate. Results The pooled analysis demonstrated no statistically significant gender-specific differences in RFS (HR = 1.0625, 95% CI 0.8094–1.0526) or PFS (HR = 1.0861, 95% CI 0.7038–1.6760). Data on CSS and OS were insufficient for meaningful conclusions. Two included studies analyzed in univariate or multivariate regression gender as risk factor for recurrence or progression, but gender was not a significant risk factor. Adverse events and QoL outcomes were notably underreported, with no gender-specific data available. Conclusions While this study found no significant gender-based differences in NMIBC outcomes following intravesical chemotherapy, the findings are limited by the small number of studies, underrepresentation of women, and inconsistent reporting of critical outcomes. Future research should prioritize gender-focused analyses and explore the molecular and genetic basis of potential differences to inform precision medicine and equitable care.